2018
DOI: 10.20882/adicciones.1050
|View full text |Cite
|
Sign up to set email alerts
|

Tipos de violencia en la infancia que inciden en el abuso y dependencia de cannabis entre adolescentes: una revisión sistemática y metaanálisis

Abstract: Resumen Abstract Tipos de violencia en la infancia que inciden en el abuso y dependencia de cannabis entre adolescentes: una revisión sistemática y metaanálisis Influence of the type of childhood violence on cannabis abuse and dependence among adolescents: a systematic review and meta-analysis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 34 publications
1
5
0
5
Order By: Relevance
“…Our study adds to this research indicating that a specific profile of externalizing, attentional and though problems characterize adolescents in TRC. These results are not surprising considering the high levels of victimization and negative parenting practices experienced by adolescents, linked to multiple mental health problems (Cornellà-Font et al, 2020;Greger et al, 2015;Leeb et al, 2011;Martínez-Mota et al, 2020;Segura et al, 2016). Our results stress the importance of providing adolescents, particularly those in TRC, with specific resources for their mental health problems.…”
Section: Discussionsupporting
confidence: 56%
“…Our study adds to this research indicating that a specific profile of externalizing, attentional and though problems characterize adolescents in TRC. These results are not surprising considering the high levels of victimization and negative parenting practices experienced by adolescents, linked to multiple mental health problems (Cornellà-Font et al, 2020;Greger et al, 2015;Leeb et al, 2011;Martínez-Mota et al, 2020;Segura et al, 2016). Our results stress the importance of providing adolescents, particularly those in TRC, with specific resources for their mental health problems.…”
Section: Discussionsupporting
confidence: 56%
“…There were conflicting findings on whether effects may differ by gender ( 32 , 40 ). Another recent review of this topic, focusing on cannabis abuse, also highlights the need for additional research on potential gender differences ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…Adverse childhood experiences such as physical and sexual abuse are known to raise risks for life course negative mental health and addiction outcomes, and the present results indicate that adolescent cannabis use may be a plausible intervention target to mitigate these risks. A recent meta-analysis of the relationship between childhood physical/sexual abuse and adolescent cannabis abuse and dependence indicated that cannabis abuse/dependence is more likely amongst those experiencing physical abuse (OR: 1.58, 95% CI 1.01–2.46), and more than twice as likely amongst those experiencing sexual abuse (OR: 2.35, 95% CI 1.64–3.35) ( 19 ). Similarly, a comprehensive meta-analysis indicated likelihood of experiencing depression or anxiety was more than twice as high amongst those reporting childhood physical abuse (OR 2.00, 95% CI 1.25–3.19) or sexual abuse (OR 2.66, 95% CI 1.88–3.75) ( 48 ), and similar results have been found in relation to the likelihood of reporting psychotic experiences in a longitudinal cohort (physical abuse AOR, 2.24 95% CI, 1.75–2.87, sexual abuse AOR, 2.04 95% CI, 1.42–2.91) ( 49 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Siguiendo la estrategia metodológica de recopilación de datos de Martínez et al (2018), dos investigadores se encargaron de realizar la revisión de documentos conforme a los descriptores y criterios de inclusión y exclusión establecidos. El grado de acuerdo en la inclusión de documentos fue de 97 %, los desacuerdos fueron atendidos por un tercer investigador que optó por incluir 100 % de la literatura científica extraída.…”
Section: Recopilación De Datosunclassified